Experiences of using the toll-free telephone line to access maternal and newborn health services in central Uganda: a qualitative study. (February 2020) - Mwase, I.; Hutchins, M.; Cameron, A.; Ware, M.; Nakanwagi, J.F.; Nakabembe, E.; Mutabazi, M.G.; Chamberlain, J.; Barageine, J.K.
Abstract: Objectives: Save the Mothers (STM) operates the toll-free telephone line (TFL) service in nine health facilities in Uganda. The TFL is influential in addressing the first and second delays in seeking care as it connects vulnerable mothers to health facilities at no cost. This study aimed at exploring the experiences of health workers and community members in using the TFL to access maternal and newborn health services in four health facilities in central Uganda. Study design: This phenomenological/qualitative study used focus group discussions (FGDs) to collect data in four health facilities. Methods: A total of 10 FGDs were conducted; two with health workers, four with women, and another four with both men and women. Each session lasted 45–60 min and had a moderator, observer, and note taker. All discussions were audio-recorded after obtaining consent from the participants. Interviews were transcribed verbatim and translated to English from audio recordings. Data analysis was performed using the thematic analysis using QDA DATA Miner software. Results: The TFL service was pivotal in improving health worker and community relations, relaying timely health advice, ensuring prompt response to obstetric emergencies and facilitated timely referrals. However, the service faced several obstacles: unanswered calls, language differences, poor connectivity/network, and misuse/abuse. Conclusion: This study demonstrates the potential of the TFL service in addressing the first and second delay as it allows for timely linkage of vulnerable mothers to health facilities. The TFL enhanced health worker and community relations and facilitated timely referrals and relaying of health advice. Addressing maternal mortality in low-income settings necessitates increased investment and scale up of such high-impact mHealth interventions. Highlights: The service was beneficial in linking vulnerable mothers to health facilities. It fostered health worker–client relations through sharing timely advice. Allowed for prompt response to obstetric emergencies and aided timely referrals. Hampered by delays in answering calls, language differences, and poor connectivity.